High fructose consumption may be associated with slow coronary flow - Mevlüt Serdar Kuyumcu; Aliye Kuyumcu (KARE Publishing, 2020)
Objective: The precise pathophysiology of slow coronary flow (SCF) has not yet been clarified; however, many studies have shown that significant fructose consumption is associated with oxidative stress and inflammation, which may play a role in the pathophysiology of SCF. The aim of this study was to investigate the association between fructose consumption and isolated SCF. Methods: Patients with stable angina pectoris who underwent coronary angiography between December 2018 and April 2019 were evaluated for this study. In all, 45 patients with isolated SCF were selected as the patient group (SCF group) and 50 patients with a normal coronary flow pattern were enrolled as a control group. Participants used a dietary record to provide details of nutrient consumption and all of the data from the 2 groups were compared. Results: The high-sensitivity C-reactive protein (Hs-CRP) level (p=0.024), white blood cell count (p=0.038), and smoking rate (p=0.012) were higher in the SCF group. Total energy (p=0.029), carbohydrate (p=0.047), and fructose consumption (p<0.001) were also higher in the SCF group. Multivariable logistic regression analysis demonstrated that a higher level of Hs-CRP, fructose consumption, and smoking were independently associated with SCF. Conclusion: The SCF group demonstrated a higher level of fructose consumption. Excessive fructose consumption may play a role in SCF pathophysiology